PERAN EKSTRAKURIKULER SENI TARI DALAM MENGEMBANGKAN MINAT DAN BAKAT SISWA DI SDN 1 ANJANI: Peran Ekstrakurikuler Seni Tari Dalam Mengembangkan Minat dan Bakat Siswa di SDN 1 Anjani - Rapikah, Kartika; M,Pd, Drs. Muchamad Triyanto; M.Pd, Muhammad Husni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to (1) determine the types of activities implemented in dance extracurricular activities at SDN 1 Anjani. (2) determine students' interest in dance extracurricular activities. (3) determine the factors that support and hinder the implementation of dance extracurricular activities in developing student interests and talents. This study used a descriptive qualitative approach to reveal the role of creativity-based extracurricular activities in the field of dance in developing student interests and talents in elementary schools. Data collection techniques included observation, interviews, and documentation. This research was conducted at SDN 1 Anjani, with the principal, supervising teachers, coaches, and students participating in extracurricular activities as subjects. Data validity was tested using source and technique triangulation. Data analysis employed the Miles & Huberman interactive model, consisting of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that creativity-based dance extracurricular activities play a significant role in fostering students' interest in the arts, increasing self-confidence, and optimally developing their movement and body movement talents. Supporting factors for these activities include support from supervising teachers, adequate facilities, student enthusiasm, and parental support. Inhibiting factors include limited practice time, differences in student abilities, and a lack of variety in materials. Therefore, it can be concluded that dance extracurricular activities at SDN 1 Anjani play a significant role in developing students' interests and talents, although there are still obstacles that the school needs to address to improve the quality of future activities.